Design Planning of Small DAM Conservation at Simple Rental Flats University of Lampung - Novitasari, Novitasari; Purwadi, Ofik Taupik; Tugiono, Subuh (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
Rain Water Harvesting is a method of water conservation by flowing rainwater into a single point of basin on the surface of the earth.  This method can be applied to areas that have a supporting topography including the educational environment.  The Lampung University area has several points of basin to hold rainwater, one of them is a water basins in the area of Simple Flats for University of Lampung can be used to do water conservation through the construction of small dam.The methods are used to redesign this small dam conservation are hydrological , small dam conservation construction planning , analysis stability of  planned constructions and the last method is estimating building construction cost.  Small dam conservation planned height of 4 m, with a base elevation at +107,00 m the dam crest elevation +110,00 m, dam crest width 2 m, the slope of 1:1,5.  The inflow debit of 0,987 m³/sec and the outflow debit of 0,586 m³/sec with cycle period 5 years. Spillway which used is free overflow type and basin specific energy building Vlugter type.  Stability small dam conservation at simple rental flats University of Lampung construction stated as safe. Reservoir volume after planned to be 29.160,750 m3, increasing from the previous volume 3.309,741 m3.  Cost estimated of design planning of conservation small dam is Rp. 7.323.901.000,00. Keywords: Small dam, Conservation, University of Lampung.